Pengaruh Terapi Tertawa Terhadap Penurunan Tekanan Darah pada Lansia Penderita Hipertensi di Panti Sosial Tresna Werdha Budi Luhur Provinsi Jambi - Poniyem; Mekeama, Luri; Nurlinawati, Nurlinawati (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2024)
Managing hypertension in older adults involves not only medication but also non-pharmacological approaches to support effective blood pressure management. One alternative approach that has gained attention is laughter therapy. Laughter is known to have relaxing effects, improve blood circulation, and reduce stress hormones, all of which contribute to lowering blood pressure. This study aims to investigate the effect of laughter therapy on blood pressure reduction in elderly individuals with hypertension at the Tresna Werdha Budi Luhur Social Home in Jambi Province. The research employs a Quasi-Experimental Pre and Post Test Control Group Design, involving 32 respondents divided into two groups (treatment and control), with sessions conducted three times a week for one month. Data were collected using observation sheets and standard operating procedures (SOP) for laughter therapy through total sampling. The results show a significant difference in blood pressure before and after laughter therapy in the treatment group, with a p-value of 0.002 (p-value < 0.005) according to the Wilcoxon test. The conclusion of this study indicates that laughter therapy significantly lowers blood pressure in elderly individuals with hypertension. Therefore, this therapy is effective as a non-pharmacological care approach for hypertensive patients, especially the elderly.